Role of multislice computed tomography in the diagnosis of acute rupture of the thoracic aorta and hepatic artery in a patient with severe concomitant injury - R. Sh. Muslimov; F. A. Sharifullin; N. R. Chernaya; M. S. Novruzbekov; L. S. Kokov (Вестник рентгенологии и радиологии, 2016)
Acute traumatic aortic rupture is associated with extremely high mortality rates and requires emergency diagnosis and treatment. This clinical example shows the role of multislice spiral computed tomography in the emergency diagnosis of rupture of two large arterial vessels in severe concomitant injury. It presents the benefits of this rapid and noninvasive imaging technique, an algorithm of the study and the semiotics of injuries in patientswith suspected traumatic aortic rupture. The paper also shows the importance of this method in defining treatment policy and then in the assessment of the results of the performed correction.